Presenteeism - Ezgi Dalkılıç; Arzu Kader Harmancı Seren (Sağlık ve Hemşirelik Yönetimi Dergisi, 2018)
Presenteeism is defined as employee's desire to be at workplace although having an illness, because of loss of job or other concerns. Nursing is ordered as one of the professional groups who experience presenteeism mostly. It was aimed to explain both the concept of presenteeism, its reasons and results and in which dimensions it affected nurses and health sector.